2017
DOI: 10.1139/apnm-2016-0413
|View full text |Cite
|
Sign up to set email alerts
|

Health care provider confidence and exercise prescription practices of Exercise is Medicine Canada workshop attendees

Abstract: Abstract:The Exercise is Medicine Canada (EIMC) initiative promotes physical activity counselling and exercise prescription within health care. The purpose of this study was to evaluate perceptions and practices around physical activity counselling and exercise prescription in health care professionals before and after EIMC training. Prior to and directly following EIMC workshops, 209 participants (physicians (n = 113); allied health professionals (AHPs) (n = 54), including primarily nurses (n = 36) and others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 28 publications
4
91
0
Order By: Relevance
“…A total of 12 studies included in this review addressed barriers to implementing PA intervention by PCPs . No studies that included rheumatologist‐addressed barriers were found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 studies included in this review addressed barriers to implementing PA intervention by PCPs . No studies that included rheumatologist‐addressed barriers were found.…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 study directly addressed barriers to PA intervention specifically for the management of knee OA . Nine studies used questionnaires to identify key barriers , and 3 studies used qualitative methods to examine attitudes and behaviors regarding exercise prescription . (Table )…”
Section: Introductionmentioning
confidence: 99%
“…Primary Care Providers (PCPs) have been identified as serving a key role in promoting PA to their patients and PCP-provided PA counselling and exercise prescription has been show to increase patients' PA levels (Dasgupta et al 2017;Orrow et al 2012). Unfortunately, only 16% of Canadian family physicians provide written PA prescriptions to their patients (Petrella et al 2007) owing to barriers including lack of time, knowledge, education, training, and lack of tools or resources reported by family physicians (Smith et al 2011;Hébert et al 2012;O'Brien et al 2017). Family physician education in specific skills of PA prescription increases physicians' self-efficacy and frequency of PA prescription to their patients (Jorgensen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that healthcare professionals have access to a large proportion of the sedentary population [7,8] and therefore, physicians have been identified as having a critical role in addressing the prevalence of physical inactivity [9]. Health care professionals(HCPs) have the best opportunity to question and counsel patients about the importance of physical activity as many people go to them for lifestyle advice [2,3,10]. They are therefore considered to be well positioned to champion the course of prevention of chronic diseases by prescribing physical activity during standard consultation [1,4] Counseling by physicians and other healthcare professionals (HCPs) has proven to be useful in helping patients improve their lifestyles [6].…”
Section: Introductionmentioning
confidence: 99%